Concreto com agregado graúdo reciclado de concreto: dosagem e produção - Santos, Ana Amélia Mota dos (2016)
A proper mix design and production must be done in order to increase the use of recycled concrete. The type of recycled aggregate (RA) used, the best replacement content, the best sequence and mixing time and the best way to evaluate the workability are some of the features that must be considered. Thus, this work was done to evaluate the mix design and production of concrete with concrete recycled coarse aggregate (RCA), using as a measure of workability the flow test in Graff’s table. Two levels of recycled coarse aggregate (20 and 40%), two levels of flow, for plastic and fluid mixtures, (350 and 400mm), and two mix design methods (IPT/EPUSP and ABCP) were evaluated on the concrete compressive strength, at 7 and 28 days of age. The results pointed out that the IPT/EPUSP mix design method was more suitable for recycled concrete. The flow test in Graff’s table, as a measure of workability, and the two stage mixture approach presented to be more suitable for the mix design and production of recycled concrete. Also, in this study, the concrete RCA content evaluated did not influence the compressive strength of concrete produced. So, it is completely feasible to use up to 40% replacement of NCA by concrete RCA.